(untitled) (Research, Society and Development, 2022)
Health education interventions aimed at the elderly, in turn, need methodologies that are more structured and adapted to the context of the elderly. It is believed that when this interest is not aroused, there is little interest and participation. For this reason, we aim to evaluate the impact of a health education proposal on the engagement of self-care in elderly people who are part of a lifelong learning project. For this, a socioeconomic and self-care assessment questionnaire was applied to the Appraisal of Self-Care Agency Scale in 14 seniors at the University of Maturity after 06 meetings. The evaluation of the workshops took place through a semi-structured questionnaire at the end of each one. Improvements were found in the ASA-A score for elderly females (p=0.040) who had more than high school education (p=0.047); part of these elderly people considered the classes as very important (p=0.001), with reports that they understood the content taught and that the speakers were able to pass on all or a good part of the content with adequate time (p=0.001). In this way, carrying out educational interventions through a methodology adapted to the group profile can provide an increase in the engagement for self-care in the elderly. Among the factors that can interfere in this change of engagement are: gender and level of education.